A Missional Hermeneutic of the Other: A Dialogue between Levinas and Confucianism - Lee, Byungohk (Missiology, 2013)
This article aims to briefly provide a missional hermeneutic of the other by undertaking a dialogue between Levinas and Confucianism. Regarding the other as heathen, uncivilized, and lost, the church has tended not to treat the other as its interlocutor. Levinas’s hermeneutic of the other might help the church correct this tendency toward the other. However, Levinas’s emphasis on the radical otherness of the other might lead to further distancing between the church and the world as the other. In this regard, Confucianism’s relational and inclusive understanding of the other might be helpful for reducing the gap between the church and the other.